Automation of Animal Feeders Using NODEMCU ESP8266 and Smartphone-Based BLYNK APP - Dali Purwanto, Timur; Effendy, Irman; Naldo, Vio (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Most humans today have used smartphones or smartphones, and besides that, humans also have pets where these pets require routine care, such as feeding the pet and others. We as humans sometimes when are not available or unable to care for our pets. Therefore the author raises the title "Automation of Animal Feeding Using Nodemcu Esp8266 and Smartphone-Based Blynk App".This research uses Research and Development methods or research and development. The source of data used in previous studies was Pet Feeder and direct observation for making the author's tool using the ADDIE method (Analysis, Design, Development, Implementation and Evaluation). Based on the observation of the finished results of the tool, it was concluded that the tool can work smoothly and show results to pets in the form of regular pet feeding schedules and with the right portions.